2019
DOI: 10.1177/1754337119853485
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics analysis of hand-cycle aerodynamics with static wheels: Sensitivity analyses and impact of wheel selection

Abstract: Aerodynamics research in cycling has underpinned innovative bicycle design, new refined riding positions and optimised rider apparel. There has been a rise in the level of aerodynamics research focused on cycling since the turn of the millennium, enabled by significant increases in computational power and the availability of software/hardware. However, cycling research has not yet fully embraced para-cycling, with limited studies conducted on the aerodynamic performance of hand-cyclists and other para-cyclists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Descriptive findings on Equipment orientated studies can be found in Table 3. One group of authors did extensive research on aerodynamics in handcycling and tandem cycling (Mannion et al, 2018a(Mannion et al, , 2018bMannion et al, 2019aMannion et al, , 2019bMannion et al, 2019c;Mannion et al, 2019d;Mannion et al, 2019e). Using computational fluid dynamics and wind tunnel tests, many different effects on aerodynamics were determined that could directly be implemented by athletes and coaches.…”
Section: Studies Related To Performance Factor "Equipment"mentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptive findings on Equipment orientated studies can be found in Table 3. One group of authors did extensive research on aerodynamics in handcycling and tandem cycling (Mannion et al, 2018a(Mannion et al, , 2018bMannion et al, 2019aMannion et al, , 2019bMannion et al, 2019c;Mannion et al, 2019d;Mannion et al, 2019e). Using computational fluid dynamics and wind tunnel tests, many different effects on aerodynamics were determined that could directly be implemented by athletes and coaches.…”
Section: Studies Related To Performance Factor "Equipment"mentioning
confidence: 99%
“…Using computational fluid dynamics and wind tunnel tests, many different effects on aerodynamics were determined that could directly be implemented by athletes and coaches. In handcycling for instance, Mazzola et al (2012) had suggested using front and rear disc wheels to reduce aerodynamic drag, but Mannion et al (2018b) further elaborated on this and indicated that disc wheels increase lateral forces and create a low-pressure region between the rear wheels (Mannion et al, 2019a). Therefore, a front disc wheel and high-rim spoked wheels constitute the best wheel configuration for handcyclists (Mannion et al, 2019e).…”
Section: Studies Related To Performance Factor "Equipment"mentioning
confidence: 99%